2011
DOI: 10.1117/12.874553
|View full text |Cite
|
Sign up to set email alerts
|

575 nm laser oscillation in Dy3+-doped waterproof fluoro-aluminate glass fiber pumped by violet GaN laser diodes

Abstract: We successfully drew a low-loss Dy-doped optical fiber (0.3dB/m at 532nm) of a waterproof fluoro-aluminate glass system and demonstrated yellow laser oscillation in the Dy 3+ -doped fluoride fiber pumped by a 398.8-nm GaN laser diode. The maximum output power was 10.3 mW and the slope efficiency was 17.1% at 575 nm. Since the fluoroaluminate-glass system has a remarkable water resistance advantage compared to ZBLAN glass, Dy-doped fluoroaluminate glass fiber is expected to contribute to making a solid-state ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Regarding the development path of Dy−doped ZBLAN materials for yellow emission, in 2001 [11], the first CW yellow emission in a Dy−doped ZBLAN fiber laser was demonstrated. Although Dy−doped yellow fiber lasers have been analyzed in some other research works [15]- [17], still the reported slope efficiencies were less than 13.2%. Indeed, in a considerable time period, due to the lack of high-performance gain fibers and high-power GaN blue lasers as the pumping sources, no significant research progress has been observed in Dy−doped fiber yellow lasers.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the development path of Dy−doped ZBLAN materials for yellow emission, in 2001 [11], the first CW yellow emission in a Dy−doped ZBLAN fiber laser was demonstrated. Although Dy−doped yellow fiber lasers have been analyzed in some other research works [15]- [17], still the reported slope efficiencies were less than 13.2%. Indeed, in a considerable time period, due to the lack of high-performance gain fibers and high-power GaN blue lasers as the pumping sources, no significant research progress has been observed in Dy−doped fiber yellow lasers.…”
Section: Introductionmentioning
confidence: 99%
“…In 2000, Limpert et al were the first to report on a Dy 3+ -doped ZBLAN fiber pumped by an argon ion laser, and they were able to resoundingly obtain a CW yellow laser [9]. In recent years, benefiting from the rapid development of high-power blue semiconductor (e.g., GaN, InGaN) laser diodes [10], an improved yellow performance has been realized in Dy 3+ -doped fibers [11]. In 2021, Zou et al reported that Dy 3+ -doped ZBLAN fibers pumped by GaN laser diodes realized yellow lasers with a maximum output of 1.12 W at 575 nm [12].…”
Section: Introductionmentioning
confidence: 99%
“…These reports highlight the favorable advantage of Dy 3+ -doped ZBLAN fibers in compact yellow lasers. However, up to now, Dy 3+ -doped fiber yellow lasers have mainly been limited to fluoride fibers [9,[11][12][13][14] which may not be helpful in high power lasers due to their relatively poor chemical stability and low laser-induced damage threshold.…”
Section: Introductionmentioning
confidence: 99%